The Role of Artificial Intelligence in Developing Applied Engineering Education and Electrical Engineering Skills in Libyan Technical Colleges (Comprehensive Journal of Science, 2026)
Artificial intelligence (AI) has increasingly influenced the evolution of engineering education, particularly within applied fields such as electrical engineering. Rather than serving solely as a technological tool, AI has begun to reshape how engineering knowledge and skills are developed. This paper examines the role of AI in advancing applied engineering education and strengthening electrical engineering competencies in Libyan technical colleges.The study critically discusses the long-standing reliance on conventional simulation tools in engineering education and argues that, while pedagogically valuable, these tools alone are insufficient to address the skill requirements imposed by the Fourth Industrial Revolution. Using a descriptive–analytical approach, relevant academic literature is reviewed, and representative AI applications in power systems, smart grids, predictive maintenance, and intelligent control are analyzed.The findings suggest that AI-based approaches enable adaptive learning, predictive reasoning, and real-time system optimization, extending beyond the capabilities of traditional simulation environments. Based on this analysis, the paper proposes practical recommendations for integrating AI into electrical engineering curricula in Libyan technical colleges to enhance graduate readiness for contemporary labor market demands.
Keywords: Artificial Intelligence, Electrical Engineering Education, Applied Engineering, Technical Colleges, Libya, Simulation Tools.